Reinventing Government in New Zealand : How Core Government Functions Benefited from Market-Type Measurement - Dale, Tony; Ball, Ian (World Bank, Washington, DC, 2012)
In the early 1990s, the New Zealand government started publishing a balance sheet and operating statement, using private sector accounting and reporting. These reports --the first such sovereign accounts anywhere-- typify reforms instituted across government trading operating, departments, and other public entities to improve performance and accountability. This note reviews the more recent reforms arising from the accounts, highlighting some of the underlying ideas that may have applications in other countries.